Performance of EncephalApp Stroop Test in Cirrhotic Patients for Evaluating Covert Hepatic Encephalopathy - Juferdy Kurniawan; Stefanus Satrio Ranty; Andri Sanityoso Sulaiman; Rino Alvani Gani (Acta Medica Indonesiana)
Background: Covert hepatic encephalopathy (HE) is the mildest HE spectrum that is difficult to detect, but associated with significant decrease in quality of life. Currently, there is no gold standard to detect covert HE. EncephalApp Stroop Test as a newer diagnostic tool is easier, faster and its ease of availability in various health institutions is expected to be applied in Indonesia for covert HE detection. This study aimed to validate and test the reliability and diagnostic ability of EncephalApp Stroop Test to diagnose covert HE, compared to the Psychometric Hepatic Encephalopathy Score (PHES) and critical flicker frequency (CFF). Methods: This study is a cross-sectional test, conducted from August to September 2018, targeted at patient with cirrhosis in Jakarta, to obtain Area Under The Curve (AUC), sensitivity, specificity, cut-off point, predictive value, likelihood ratio, and post-test probability of the EncephalApp Stroop Test, compared to PHES and CFF. The Validity and reliability tests were done before diagnostic study. Translation of the EncephalApp Stroop Test were first carried out using WHO protocol. All patients first underwent a Mini Mental State Examination and Ishihara Test to rule out color blindness. Results: Thirty subjects participated in validity and reliability tests, and eighty in diagnostic tests. The translated application showed excellent internal consistency (Chronbach’s Alpha of 0.942) and correlation coefficient of 0.82. The diagnostic study showed OnTime + OffTime as the best parameter (AUC: 0.897 (95% CI: 82.9% - 96.5%); sensitivity: 88.6%; specificity: 80%; positive predictive value (PPV): 0.77; negative predictive value (NPV): 0.9; positive likelihood ratio (LK+): 4.4; negative likelihood ratio (LK-): 1.4; positive post-test probability: 0,775; negative post-test probability: 0,1; and cut-off point ≥ 188.8 seconds. Conclusion: The EncephalApp Stroop Test is valid and reliable, with good AUC value, sensitivity, specificity, PPV, NPV and likelihood ratio in diagnosing covert hepatic encephalopathy in patients with cirrhosis in Indonesia.